2018
DOI: 10.1016/j.nicl.2018.02.030
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between muscarinic M1 receptor binding and cognition in medication-free subjects with psychosis

Abstract: BackgroundIt is still unclear which underlying mechanisms are involved in cognitive deficits of psychotic disorders. Pro-cognitive effects of muscarinic M1 receptor agonists suggest alterations in M1 receptor functioning may modulate these symptoms. Post mortem studies in patients with schizophrenia have shown significantly reduced M1 receptor expression rates in the dorsolateral prefrontal cortex (DLPFC) compared to controls. To date no in-vivo examinations of M1 receptor binding in relation to cognitive impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 47 publications
1
26
0
Order By: Relevance
“…This is important because it is argued such drugs will be a new treatment for schizophrenia (Conn et al, 2009). However, the use of either SPECT (Raedler et al, 2003; Bakker et al, 2018) or PET would be advisable to determine if participants with a marked loss of CHRM1s and schizophrenia had been recruited into drug trials of CHRM1 allosteric modulators to treat the disorder.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is important because it is argued such drugs will be a new treatment for schizophrenia (Conn et al, 2009). However, the use of either SPECT (Raedler et al, 2003; Bakker et al, 2018) or PET would be advisable to determine if participants with a marked loss of CHRM1s and schizophrenia had been recruited into drug trials of CHRM1 allosteric modulators to treat the disorder.…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing body of evidence that includes data from neuroimaging, postmortem CNS, and preclinical pharmacology suggesting that there is a role for the muscarinic M1 receptor (CHRM1) in the pathophysiology and treatment of schizophrenia (Raedler et al, 2007; Gibbons and Dean, 2016). Center to this hypothesis was evidence to suggest there were lower levels of CHRM1s in many CNS regions in participants with the disorder (Raedler et al, 2003) and that levels of CHRM1 in the dorsolateral prefrontal cortex were inversely related to cognitive ability and correlated with the severity of negative symptoms (Bakker et al, 2018). Notably, soon after the demonstration of lower levels of CHRM1 in the CNS from participants with schizophrenia, it was suggested that activating the CHRM1 could prove to have therapeutic benefits for those with the disorder (Felder et al, 2001; Dean et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In schizophrenia, altered cholinergic neurotransmission is intimately linked to the defective cognitive functions associated primarily with cortical and hippocampal regions. Post-mortem studies consistently reported transcriptional and proteomic alterations in M 1 and M 4 receptors in the hippocampus [ 112 , 113 ] prefrontal and frontal cortices [ 112 , 114 , 115 , 116 ], and also cingulate cortex [ 117 , 118 ] of schizophrenic patients. Conversely, potentiation of the central muscarinic system by M 1 mAChR’s positive allosteric modulator (PAM), completely restored defective long-term depression as well as impairments in the cognitive function and social interaction in PCP-treated mouse model of schizophrenia [ 119 ].…”
Section: Cholinergic Receptorsmentioning
confidence: 99%
“…NEUROSCIENTISTS DO Figure 1 shows a simplified example of a magnetic resonance spectroscopy (MRS) work flow commonly used to examine neurochemical mechanisms and drug efficacy in neuropsychiatric and neurological disorders (e.g., [2,11]). Dealing with multi-vendor data is common due to use of historical data, multi-site scanning, consortium data, vendor switching within hospitals, research dedicated versus clinical scanners, PET-MRI combined machines, and level of investment from vendors to advance new sequences.…”
Section: The Programming Thatmentioning
confidence: 99%